PENDEKATAN â EMPAT P â DALAM KEGIATAN PENDIDIKAN DAN PEMBELAJARAN - Fitriani, Aries (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
Learning is closely related with how to educate learners and set up the learning process that best suits on the studentsâ need so as to make the process running effectively and meaningfully and learners can encourage themselves achieve the objectives as what is actualized in the curriculum. The scholars and experts in education have been trying to develop various methods and approaches that can be used by educators in the learning process. The teachersâ ability in selecting and determining the approach to learning will greatly impact the effectiveness of learning itself. This article attempts to discuss and explain the concept of a "Four P" approach (Pribadi, Pendorong, Proses, and Produk) which refers to four main good learning practices covering personality, encouragement, process, and Product that can be developed and implemented contextually by educators in the learning activities of Islamic Education. The ultimate objective of this sort of approach is that how teachers help learners achieve the objective of learning, facilitate them to learn the subject matter easily, increase their competence, develop their talents and interests in the learning process, guide them to solve their academic problems, create fun learning and satisfaction, and gain a skillful, religious and intellectuals learners who can meet the needs and demands of the society.Â ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙØªØ¹ÙÙ Ø¨ÙÙÙÙØ© ØªØ¯Ø±ÙØ¨ Ø§ÙØ·ÙØ§Ø¨ Ø¹ÙÙ Ø£Ù ÙØªØ¹ÙÙÙØ§ Ø¨Ø£ÙÙØ³ÙÙ Ø£ÙØ±Ø§ ÙØ§ÙÙØ§. ÙÙØ¯ ÙØ§Ù Ø§ÙØªØ±Ø¨ÙÙÙÙ Ø¨ØªÙÙÙØ© Ø¹Ø¯ÙØ© ÙØ¯Ø§Ø®Ù ÙØ§ÙØ·Ø±Ù Ø§ÙØªÙ ÙØµÙØ Ø§Ø³ØªØ®Ø¯Ø§ÙÙØ§ ÙÙÙØ¹ÙÙÙÙ ÙÙ Ø¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙÙ. ÙÙØ¯Ø±Ø© Ø§ÙÙØ¯Ø±Ø³ Ø¹ÙÙ Ø§Ø®ØªÙØ§Ø± Ø§ÙÙØ¯Ø®Ù Ø§ÙÙÙØ§Ø³Ø¨ ØªØ¤Ø«Ø± ÙÙ ÙØ¬Ø§Ø Ø§ÙØªØ¯Ø±ÙØ³ . ØØ§ÙÙ ÙØ°Ø§ Ø§ÙÙÙØ§Ù Ø§ÙØ¨ØØ« Ø³ÙØ§ÙÙØ§ ÙÙ ÙØ§ ÙØ³ÙÙÙ Ø¨ÙØ¯Ø®Ù ( Empat P ) ÙÙØ´ÙÙ Ø§ÙØ´Ø®ØµÙØ© Ù Ø§ÙØ¯ÙØ§ÙØ¹ Ù Ø§ÙØ¹ÙÙÙØ© ÙØ§ÙØ§ÙØªØ§Ø¬Ø Ø§ÙØªÙ ÙÙÙÙ ØªÙÙÙØªÙØ§ ÙØªØ·Ø¨ÙÙÙØ§ ÙÙÙØ¯Ø±Ø³ÙÙ Ø®ÙØ§Ù ØªØ¯Ø±ÙØ³ÙÙ ÙØ§Ø¯Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ©. ÙØ§Ù ÙØ°Ø§ Ø§ÙÙØ¯Ø®Ù â ÙØ¯Ù ÙØ¯Ø±Ø³Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© â ÙÙ ÙÙÙ Ø§ÙØØµÙÙ Ø¹ÙÙ ØªØ¹ÙÙ Ø§ÙÙØ§Ø¯Ø© ÙÙÙÙÙ Ø§ÙØ§ÙÙØ§ÙØ§Øª ÙØ§ÙÙÙÙÙ ÙØ¯Ù Ø§ÙØ·ÙØ§Ø¨ Ø®ÙØ§Ù Ø§ÙØ¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙÙÙØ©Ø ÙØÙÙ ÙØ´Ø§ÙÙÙÙØ ÙÙÙØªÙØ¹ Ø§ÙÙØ¯Ø±Ø³ Ø¨Ø§ÙØªØ¯Ø±ÙØ³ Ø ÙÙØ¬ÙØ¯ Ø§ÙØ§ÙØªØ§Ø¬ Ø§ÙØ¨Ø´Ø±Ù Ø§ÙÙØ¨ØªÙØ± Ø§ÙØµØ§ÙØ ÙØ§ÙÙÙÙØ± ÙØ§ÙÙØ§Ø¯Ø± Ø¹ÙÙ Ø§ÙÙÙØ§Ø¡ Ø¨ÙØªØ·ÙØ¨Ø§Øª Ø§ÙÙØ¬ØªÙØ¹ ÙØØ§Ø¬Ø§ØªÙÙ.